Expanding the mutational spectrum in Johanson‐Blizzard syndrome: identification of whole exon deletions and duplications in the UBR1 gene by multiplex ligation‐dependent probe amplification analysis. Issue 6 (31st July 2017) - Sukalo, Maja; Schäflein, Eva; Schanze, Ina; Everman, David B.; Rezaei, Nima; Argente, Jesús; Lorda‐Sanchez, Isabel; Deshpande, Charu; Takahashi, Tsutomu; Kleger, Alexander; Zenker, Martin
Abstract: Background: Johanson‐Blizzard syndrome (JBS, MIM #243800) is a very rare autosomal recessive disorder characterized by exocrine pancreatic insufficiency, nasal wing hypoplasia, hypodontia, and other abnormalities. JBS is caused by mutations of the UBR1 gene (MIM *605981), encoding a ubiquitin ligase of the N‐end rule pathway. Methods: Molecular findings in a total of 65 unrelated patients with a clinical diagnosis of JBS who were previously screened for UBR1 mutations by Sanger sequencing were reviewed and cases lacking a disease‐causing UBR1 mutation on either one or both alleles were included in this study. In order to discover mutations that are not detectable by Sanger sequencing, we designed a probe set for multiplex ligation‐dependent probe amplification (MLPA) analysis of the UBR1 gene and analyzed the copy number status of all 47 UBR1 exons. Results: Our previous studies using Sanger sequencing could detect mutations in 93.1% of 130 disease‐associated UBR1 alleles. Six patients with a highly suggestive clinical diagnosis of JBS and unsolved genotype were included in this study. MLPA analysis detected six alleles harboring exon deletions/duplications, thereby raising the mutation detection rate in the entire cohort to 97.7% (127/130 alleles). Conclusion: We conclude that single or multi‐exon deletions or duplications account for a substantial proportion of JBS‐associated UBR1 mutations. Abstract : Johanson‐Blizzard syndrome is a very rare autosomal recessive disorder caused by mutations of the UBR1 gene. Sanger sequencing could detect mutations in 93.1% of 130 disease‐associated UBR1 alleles. Six patients with a highly suggestive clinical diagnosis of JBS and unsolved genotype were included in this multiplex ligation‐dependent probe amplification (MLPA) study, raising the mutation detection rate in the entire cohort to 97.7% (127/130 alleles).